Assessment of Serum High Density Lipoprotein, Low Density Lipoprotein, and Very Low Density Lipoprotein in Bipolar Disorder Subjects - Tehmina Tariq, Sana Sarmad, Amna Noor, Saher Sarmad, Shanza Tariq, Nabeel Ibad, Javed Anver Qureshi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Bipolar disorder (BD) is a psychiatric condition and is defined as mood swings that alternate between mania, hypomania, and depression. Studies have been conducted globally to assess lipid profile (High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL), and Very Low Density Lipoprotein (VLDL)) for BD with varying results. No such studies have been conducted in Pakistan. Therefore, current study was designed to assess lipid profile (HDL, LDL, VLDL) in clinically diagnosed bipolar BD. Materials and Methods: One hundred and twelve blood samples were collected of diagnosed BD patients visiting Sheikh Zayd Hospital (SZH) and Punjab Institute of Mental Health (PIMH) Lahore. HDL, LDL and VLDL were estimated using standard biochemical methods. Results: Results obtained were statistically analyzed using SPSS. A total of 112 BD patients, 48 (58.5%) were manic, 26 (31.7%) were depressive, 8 (9.8%) were euthymic. The mean HDL (41.26±12.57 mg/dl), LDL level (115.15±38.26 mg/dl) in bipolar group (manic, depressive and euthymic) as compared to control group were statistically significant with p-value 0.026. The mean VLDL level (33.17±18.43 mg/dl) level in bipolar and control groups was statistically insignificant with p-value 0.609. Conclusions: The present study suggests that HDL level is decreased in manic BD patients. The raised value of LDL-C is found in depressive and euthymic patients. VLDL level was same in BD and control groups. Keywords: Bipolar Disorder, Lipid Profile, High Density Lipoprotein, Low Density Lipoprotein, Very Low Density Lipoprotein